Optimisation of the structure of a helicopter blade in view of reducing cabin vibration - Tixadou, E.; Coisnon, R. (My University, 2021)
The study presented in this paper aims at bringing the blade internal structure into a global multi-physics optimization of the helicopter rotor. The optimization is applied to vibration reduction in forward flight with aeroelastic and multidisciplinary constraints. The objective function consists of the dynamic hub loads, and behaviour constraints are imposed on dynamics, performance and manufacturability criteria. A genetic algorithm is used to conduct a global search of the design space among numerous combinations of blade physical parameters with discrete values (positioning of tuning masses, composite skin layers, counterweight materials…). The novelty brought by this study includes simulations integrated in a tool-chain based on physical parameters with manufacturability constraints